2021
DOI: 10.1002/ptr.7022
|View full text |Cite
|
Sign up to set email alerts
|

Icarisid II promotes proliferation and neuronal differentiation of neural stem cells via activating Wnt/β‐catenin signaling pathway

Abstract: Adult neurogenesis plays a vital role in maintaining cognitive functions in mammals and human beings. Mobilization of hippocampal neurogenesis has been regarded as a promising therapeutic approach to restore injured neurons in neurodegenerative diseases including Alzheimer's disease (AD). Icarisid II (ICS II), an active ingredient derived from Epimedii Folium, has been reported to exhibit multiple neuroprotective effects. In the present study, we investigated the effects of ICS II on the proliferation and diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Evidence has confirmed that repression of Wnt/β‐catenin pathway contributes to neurogenesis dysfunction in AD patients and animals (Choi & Tanzi, 2019; Fatt et al, 2015; Jia et al, 2019), while activation of Wnt/β‐catenin pathway facilitates the survival, self‐renewal, and maturation of NSCs, as well as suppresses Aβ expression (Menet, Bourassa, Calon, & ElAli, 2020). We have previously identified that ICS II could activate Wnt/β‐catenin cascade to potentiate the proliferation and neuronal differentiation of APP‐NSCs in vitro (Xiao et al, 2021). Thus, in the present study, we intraperitoneally administrated APP/PS1 mice with XAV‐939, an inhibitor of Wnt/β‐catenin cascade promoting the degradation of β‐catenin (Almasoud et al, 2020; Huang et al, 2009), to further investigate whether this pathway participates in the improvement of neurogenesis caused by ICS II.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence has confirmed that repression of Wnt/β‐catenin pathway contributes to neurogenesis dysfunction in AD patients and animals (Choi & Tanzi, 2019; Fatt et al, 2015; Jia et al, 2019), while activation of Wnt/β‐catenin pathway facilitates the survival, self‐renewal, and maturation of NSCs, as well as suppresses Aβ expression (Menet, Bourassa, Calon, & ElAli, 2020). We have previously identified that ICS II could activate Wnt/β‐catenin cascade to potentiate the proliferation and neuronal differentiation of APP‐NSCs in vitro (Xiao et al, 2021). Thus, in the present study, we intraperitoneally administrated APP/PS1 mice with XAV‐939, an inhibitor of Wnt/β‐catenin cascade promoting the degradation of β‐catenin (Almasoud et al, 2020; Huang et al, 2009), to further investigate whether this pathway participates in the improvement of neurogenesis caused by ICS II.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggested that ICS II could attenuate neuroinflammation in rats injured by lipopolysaccharide (Zhou et al, 2019), alleviate hippocampal damages and improve cerebral microcirculatory in gerbils suffering from ischemia‐reperfusion (Yan et al, 2014), rescue neuronal degeneration by suppression of Aβ production in AD mouse model (Yan et al, 2017), as well as improve cognitive function by potentiation of the synaptic plasticity in rats injured by chronic cerebral hypoperfusion (Liu, He, Yan, Kuang, & Yu, 2019). Moreover, using by primary cultured NSCs overexpressed APPswe gene variant (APP‐NSCs), we previously confirmed that ICS II could restore the dysfunction of proliferation and differentiation of APP‐NSCs via triggering the activation of Wnt/β‐catenin cascade, as well as stimulate primary cultured astrocytes secretion of Wnt‐3a facilitating neuronal differentiation of APP‐NSCs (Xiao et al, 2021). However, whether ICS II could trigger hippocampal neurogenesis to recover the damaged neurons and cognitive dysfunction in AD pathological conditions has not been clearly explored.…”
Section: Introductionmentioning
confidence: 85%
“…Neurosphere formation assay was used to evaluate the effect of PA on proliferation of APP-expressing NSCs as our previous report . Briefly, GFP- or APP-expressing NSCs were cultured in proliferation medium in the presence or absence of PA.…”
Section: Methodsmentioning
confidence: 99%
“…Neurosphere formation assay was used to evaluate the effect of PA on proliferation of APPexpressing NSCs as our previous report. 11 Briefly, GFP-or APPexpressing NSCs were cultured in proliferation medium in the presence or absence of PA. The number and diameter of neurospheres were captured by fluorescence microscope and analyzed using ImageJ software after 5 days.…”
Section: Ecd Calculationmentioning
confidence: 99%
See 1 more Smart Citation